Attaining exceptional electrical conductivity in Cu-Fe composite by powder rolling strategy. (1st April 2023) - Tian, Y.Z.; Peng, S.Y.; Yang, Y.; Pang, X.Y.; Li, S.; Jiang, M.; Li, H.X.; Wang, J.W.; Qin, G.W.
Abstract: The application of immiscible Cu-Fe composite was limited due to the severe Fe macrosegregation and low electrical conductivity. In this work, bulk Cu-10Fe composite was prepared by powder rolling strategy and further cold rolled to foils. The composition distribution, microstructure evolution, electrical property and mechanical property were studied. The mutual diffusion of Cu and Fe elements are well controlled during the powder rolling process, such that the good electrical conductivity of the Cu matrix is retained. The Fe particles distribute homogeneously in the Cu matrix, eliminating the Fe macrosegregation phenomenon during the casting process. The Cu-10Fe composite possesses tensile strength of 507 MPa and electrical conductivity of 80.1% IACS. Strengthening mechanisms and origins of exceptional electrical properties were discussed. Graphical abstract: Image, graphical abstract